2022
DOI: 10.14336/ad.2022.0103
|View full text |Cite
|
Sign up to set email alerts
|

MiR-4763-3p targeting RASD2as a Potential Biomarker and Therapeutic Target for Schizophrenia

Abstract: Existing diagnostic methods are limited to observing appearance and demeanor, even though genetic factors play important roles in the pathology of schizophrenia. Indeed, no molecular-level test exists to assist diagnosis, which has limited treatment strategies. To address this serious shortcoming, we used a bioinformatics approach to identify 61 genes that are differentially expressed in schizophrenia patients compared with healthy controls. In particular, competing endogenous RNA network revealed the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Immunoblotting analysis was performed as described previously [ 26 ]. In detail, wash the cells with pre-cooled PBS and lyse them on ice with Western and IP lysate (Beyotime, China) for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting analysis was performed as described previously [ 26 ]. In detail, wash the cells with pre-cooled PBS and lyse them on ice with Western and IP lysate (Beyotime, China) for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we screened and found that miR-4763-3p is dysregulated in the early stages of AD and is positively correlated with age. Previous research [20] has shown that miR-4763-3p is closely related to cognition. Therefore, we further explored its ameliorative effect on cognitive decline in early-stage AD.…”
Section: Introductionmentioning
confidence: 92%
“…According to the study, only hsa-miR- 4763-3p, hsa-miR-342-3p, hsa-miR-361-3p, hsa-miR-485-3p and hsa-miR-211-5p are thought to be cognitively relevant [20,[23][24][25][26]. We examined miRNA expression in the hippocampal tissues of AD-MCI and WT mice at 6 and 12 months.…”
Section: Mir-4763-3p Antagomir Ameliorates Cognitive Decline In Ad-mc...mentioning
confidence: 99%
“…focused on the abnormally expressed miR-4763-3p through biological information, and the expression change was also confirmed in patients with schizophrenia (Wang et al ., 2022). Moreover, miR-4763-3p inhibition can alleviate the symptoms of schizophrenia by targeting RASD2 in schizophrenia model mice (Wang et al ., 2022). Recently, Davarinejad et al .…”
Section: Introductionmentioning
confidence: 94%